2022
DOI: 10.5194/hess-26-1481-2022
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting changes in hydrological processes of the Volta River basin under global warming

Abstract: Abstract. A comprehensive evaluation of the impacts of climate change on water resources of the West Africa Volta River basin is conducted in this study, as the region is expected to be hardest hit by global warming. A large ensemble of 12 general circulation models (GCMs) from the fifth Coupled Model Intercomparison Project (CMIP5) that are dynamically downscaled by five regional climate models (RCMs) from the Coordinated Regional-climate Downscaling Experiment (CORDEX)-Africa is used. In total, 43 RCM–GCM co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 137 publications
(121 reference statements)
0
12
0
Order By: Relevance
“…In this regard, it should be outlined that the use of the MERRA-2 reanalysis data helped in representing spatial patterns in the rainfall over the catchment, which was certainly critical in attaining optimal model calibration. Therefore, the potential of using reanalysis datasets in hydrological modeling should be further explored as a potential and viable pathway to improve hydrological modeling efforts in data-scarce, poorly gauged, or even ungauged catchments, which are quite common in the West African Sahel [19,42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, it should be outlined that the use of the MERRA-2 reanalysis data helped in representing spatial patterns in the rainfall over the catchment, which was certainly critical in attaining optimal model calibration. Therefore, the potential of using reanalysis datasets in hydrological modeling should be further explored as a potential and viable pathway to improve hydrological modeling efforts in data-scarce, poorly gauged, or even ungauged catchments, which are quite common in the West African Sahel [19,42].…”
Section: Discussionmentioning
confidence: 99%
“…This vulnerability arises from the heavy reliance on water resources to sustain vital sectors such as agriculture and livestock husbandry and the indispensable provision of potable water to local populations [2,3,16,17]. Within the Mouhoun River Catchment (MRC), located in the south-western region of the country, 14,900 km 2 in size, the situation is further compounded by the escalating impact of climate change on water resources [18,19]. The MRC is of specific importance in Burkina Faso for several reasons: in terms of water supply, the Mouhoun River is the largest in Burkina Faso, and the catchment provides drinking water (to over 10 million people), irrigation (over 200,000 ha), and livestock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, few modelling studies in the Sahel have been dedicated to this exercise still [Aich et al, 2015, Akoko et al, 2021, Angelina et al, 2015, Dembélé et al, 2022, Karambiri et al, 2011, Séguis et al, 2004. Among the reasons often put forward, some authors mention the difficulty in representing accurately Sahelian hydrological processes in most of the available models [Cornelissen et al, 2013, Karambiri et al, 2003, or the data scarcity [Mahé and Paturel, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Distributed process-based hydrological models allow spatial estimates of hydrological fluxes and states (Fatichi et al, 2016), even at large scales and hyper-resolutions (< 1 km, Bierkens et al (2015)). Such models are increasingly being used for assessments of climate change impacts on droughts (Van Huijgevoort et al, 2014;Cammalleri et al, 2020b;Dembélé et al, 2022), drought monitoring (Cammalleri et al, 2017(Cammalleri et al, , 2020aSaha et al, 2021), forecasting (Trambauer et al, 2015;Van Hateren et al, 2019;Sutanto et al, 2020), and drought studies in general (Mastrotheodoros et al, 2020;Yang et al, 2021;Rakovec et al, 2022). However, some studies revealed reduced model performances when simulating streamflow droughts (Kumar et al, 2022) and their generating processes (Van Loon et al, 2012;Avanzi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%